1989
DOI: 10.1161/01.str.20.5.652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monosialoganglioside inner ester on neurologic recovery after global cerebral ischemia in monkeys.

Abstract: We assessed the consequences of transitory global cerebral ischemia and the influence of monosialoganglioside inner ester (AGF 2) treatment on neurologic outcome, cerebral blood flow, and cerebral metabolic rate in monkeys over 48 hours. Global cerebral ischemia was produced by a cervical tourniquet and a lowering of blood pressure to 6.65 kPa; recirculation followed after 30 minutes. AGF 2 (30 mg/kg) was administered intravenously immediately after initiation of recirculation and intramuscularly twice a day f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Our laboratories previously reported that acute GM 1 treatment significantly reduced mortality and injury in global ischemia (Karpiak et al, 1987a;Mahadik et al , 1988). Subsequently, others have reported that GMl is effective in reducing CNS ischemic injury (Cahn et al, 1989;KOmatsumoto et al, 1988;Urbanics et al, 1989;Mazzari et al, 1990;Skaper et al, 1989). Recent clinical studies support the efficacy of ganglioside treatment for CNS ischemia (Argentino et al, 1989).…”
Section: Tissue Sampling: Primary Infarct and Peri-ischemic Areasmentioning
confidence: 92%
“…Our laboratories previously reported that acute GM 1 treatment significantly reduced mortality and injury in global ischemia (Karpiak et al, 1987a;Mahadik et al , 1988). Subsequently, others have reported that GMl is effective in reducing CNS ischemic injury (Cahn et al, 1989;KOmatsumoto et al, 1988;Urbanics et al, 1989;Mazzari et al, 1990;Skaper et al, 1989). Recent clinical studies support the efficacy of ganglioside treatment for CNS ischemia (Argentino et al, 1989).…”
Section: Tissue Sampling: Primary Infarct and Peri-ischemic Areasmentioning
confidence: 92%
“…Beneficial effects of gangliosides have been reported in other animal models of ischemia Cahn et al, 1986Cahn et al, , 1989Karpiak et al, 1987Karpiak and Mahadik, 1990;Bharucha et al, 1989) and in stroke patients (Bassi et al, 1986;Argentino et al, 1989;Karpiak and Mahadik, 1990). We have hypothesized that these effects are due to a protection of plasma membrane function through stabilization of its structural integrity.…”
Section: Introductionmentioning
confidence: 88%
“…This relationship between GMl and trophic factors is noteworthy since it has been suggested that Na + ,K + -ATPase losses in damaged neurons are protected by NGF (Demediuk et al, 1985;Sendtner et al, 1988). Lastly, there are reports that GMl acutely affects cerebral blood flow (CBF) reperfusion after arterial occlusion (Greenberg et al, 1986;Cahn et al, 1986Cahn et al, , 1989. This hypothesis is notable, since GM1 is Shawn to protect the CNS cholinergic system (Maysinger et al, 1988;Cuello et al, 1989), which has been implicated in the regulation of CBF (Scremin and Scremin, 1986).…”
Section: Molecular Mechanismsmentioning
confidence: 95%
“…10 The molecular mechanisms underlying the capability of siagoside to limit neuronal damage after a cerebral hypoxic/ischemic insult remain to be fully denned. When added to cultured neuronal cells, monosialogangliosides are stably incorporated into the outer layer of the cell membrane in a temperature-, time-, and concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%